Estudo da qualidade da matéria-prima de uma fábrica de ração para frangos de corte utilizando cartas de controle e técnicas Taguchi de custo mínimo - 2005 - Vilas Boas, Érika Bastos Buttenmüller (2005)
The objective of this work was to verify the statistical quality control of the raw material used during the manufacturing of animal feed, which is being utilized for broiler chicken feed in businesses located in the western region of the state of Paraná. The raw material selected to be monitored were: corn and soy meal from vegetable origin, and meat flour, viscus and feather flour from animal origin. The variables that make up each group of raw material, such as humidity, raw protein, soluble protein, phosphorus, acidity, raw fiber, uretic activity and ethereal extract were collected during 2003 and 2004. The focus of this study of quality was on the application of individual X and AM control charts, and EWMA charts, Tabular CUSUM accumulated sum charts and V Mask CUSUM. An approach regarding the cost of quality loss was utilized in order to determine the economic interval of inspection related to the minimum cost, according to Taguchi s techniques. Regarding the corn raw material, the results show that the pondered control chart EWMA was the most efficient when analyzing the studied variables. As far as the capability of the process is concerned, we can conclude that only the humidity variable is below the desired specifications. The soy meal raw material had the individual X and AM charts as the most efficient and with an equivalent performance, and, regarding the process capacity, only the variable urease is up to the minimum value recommended by the CBAA. When it comes to the meat flour raw material, the tabular of the accumulated sums chart CUSUM was the least efficient and, as far as its process capacity is concerned, only the humidity variable is up to the minimum requirements required by the CBAA. Regarding the feather flour raw material, the individual AM chart was the most efficient, as far as the process capacity is concerned, none of the variables are up to the minimum specifications required by the CBAA. When it comes to the viscus flour raw material, the EWMA chars and the Tabular CUSUM were the most efficient, having an equivalent performance, and regarding the process capacity, only the humidity and acidity variables are up to minimum CBAA requirements. For the analysis of the minimum costs, we observed that the costs increase with the process tolerance increase (k) and decrease with the increase of the Cpl or Cpu values. Regarding the optimum interval analysis of inspection, the results show that the interval times decrease with the increase of the process tolerance (k), and increase with the increase of the values of Cpl or Cpu.